Evolution of Cerebral Atrophy in a Patient with Super Refractory Status Epilepticus Treated with Barbiturate Coma - Newey, Christopher R. (Case Rep Neurol Med, 2017)
Introduction. Status epilepticus is associated with neuronal breakdown. Radiological sequelae of status epilepticus include diffusion weighted abnormalities and T2/FLAIR cortical hyperintensities corresponding to the epileptogenic cortex. However, progressive generalized cerebral atrophy from status epilepticus is underrecognized and may be related to neuronal death. We present here a case of diffuse cerebral atrophy that developed during the course of super refractory status epilepticus management despite prolonged barbiturate coma. Methods. Case report and review of the literature. Case. A 19-year-old male with a prior history of epilepsy presented with focal clonic seizures. His seizures were refractory to multiple anticonvulsants and eventually required pentobarbital coma for 62 days and midazolam coma for 33 days. Serial brain magnetic resonance imaging (MRI) showed development of cerebral atrophy at 31 days after admission to our facility and progression of the atrophy at 136 days after admission. Conclusion. This case highlights the development and progression of generalized cerebral atrophy in super refractory status epilepticus. The cerebral atrophy was noticeable at 31 days after admission at our facility which emphasizes the urgency of definitive treatment in patients who present with super refractory status epilepticus. Further research into direct effects of therapeutic coma is warranted.